Relationship between professional identity and academic performance of medical undergraduates in China: the mediating role of self-efficacy - Zhang, Ge (Frontiers in Medicine, 2025)
IntroductionUndergraduates’ academic performance is susceptible to psychological factors. This study focused on investigating the relationship between professional identity, self-efficacy and academic performance of medical undergraduate and further explored the mediating role of self-efficacy.MethodsThis study used quantitative research method to collect data from 350 five-year clinical medical undergraduates through an online survey. These participants completed the Professional Identity Questionnaire and the Academic Self-Efficacy Questionnaire, while the researcher assessed their academic performance by counting their GPAs. Correlation analysis was used to explore the relationship between professional identity, self-efficacy, and academic performance, and the mediating effect of self-efficacy was tested through the PROCESS macro of SPSS.ResultsThe results showed that there was a positive correlation between medical undergraduates’ professional identity and academic performance, but the correlation between them was weak (r = 0.253, p < 0.001), and there was a significant positive correlation with self-efficacy of moderate strength (r = 0.604, p < 0.001). There is a significant positive correlation between self-efficacy and academic performance and the correlation coefficient is greater than 0.7, which is a very strong correlation. Moreover, the mediating effect of self-efficacy between professional identity and academic performance was established and the mediating effect accounted for 85.51% of the total effect.DiscussionThis study contributes to the understanding of the relationship between professional identity, self-efficacy and academic performance of medical undergraduates. There is a correlation between professional identity, self-efficacy and academic performance, but the correlation between self-efficacy and academic performance is the strongest, the correlation between professional identity and self-efficacy is only moderate, and the correlation between professional identity and academic performance is the weakest. Therefore, it is recommended that medical universities and teachers pay great attention to the cognitive and psychological status of medical undergraduates, especially to the mediating role of self-efficacy, so as to help medical undergraduates to improve their academic performance in a targeted way.